Impact of Maternal Age on Oocyte and Embryo Competence - Cimadomo, Danilo; Fabozzi, Gemma; Vaiarelli, Alberto; Ubaldi, Nicolò; Ubaldi, Filippo Maria; Rienzi, Laura (Frontiers in Endocrinology, 2018)
The overall success of human reproduction, either spontaneously or after IVF, is highly dependent upon maternal age. The main reasons for age-related infertility includes reduced ovarian reserve and decreased oocyte/embryo competence due to aging insults, especially concerning an increased incidence of aneuploidies and possibly decreased mitochondrial activity. Age-related chromosomal abnormalities mainly arise because of meiotic impairments during oogenesis, following flawed chromosome segregation patterns such as non-disjunction, premature separation of sister chromatids or the recently-described reverse segregation. In this review, we briefly discuss the main mechanisms putatively impaired by aging in the oocytes and the deriving embryos. We also report the main strategies proposed to improve the management of advanced maternal age women in IVF: fertility preservation through oocyte cryopreservation to prevent aging; optimization of the ovarian stimulation and enhancement of embryo selection to limit its effects; and oocyte donation to circumvent its consequences.